The Echoes of International Human Rights Law: In Perspective of Law Enforcement Dimension to Deal with Irregular Immigrants in Indonesia - Indra, Muhammad (Indonesian Journal of International Law, 2021)
International human rights laws in the forms of United Nations Statues, International Conventions, Universal Declaration on Human Rights and other international law instruments have highlighted a guarantee of humanitarian protection which echoing human rights components without exception inborn to human being in particular refugees as the subject of international law. In managing minimum standard of rights and duties of a refugee and the judicial status of refugee under the protection of UNHCR and IOM humanitarian efforts within Indonesian territorial jurisdiction it is required the all of refugees and asylum seeker abide to national regulation and legislation formats while they are residing temporarily in Indonesia Until currently, the policies of Indonesian Government in dealing with and handling or doing management efforts for the arrival of refugees and asylum seekers in Indonesia, have not emerged yet. Considering the challenge on how to deal with asylum seekers and refugees be categorized as irregular immigrants, this issue needs mitigation effort by formulating the Directorate General of Immigration’s policy to be more focus and comprehensive to cope with adverse negative impacts of the existence of illegal immigrants undergoing to the matters of ideology, politics, economy, social cultural extend, national security and immigration compliance.